O roteiro como interface entre literatura e cinema: O texto escrito que vira imagem, ação e som - Rocha, Christiane Maria Pereira (2020)
This research presents an investigative study on the methodology applied to literary reading practices for Elementary School II students and rereading / interpretation with the possibility of transposing the written book into an audiovisual production going through the writing of an adaptation script. It was accomplished with second-to last students from Escola Estadual Marcolino de Barros, in Patos de Minas, MG. The main objective of this study was to expand the possibilities of evaluation / work of literary readings from written to audiovisual language, with literary literacy as a priority. To this end, we initially carried out an investigation about the students' interests in reading and how they perceive the presence of literature in other artistic manifestations, such as cinema. At first, bibliographic research on literary reading, cinema, the relationship between literature and cinema and the adaptation processes were carried out, as well as the analysis of official texts guiding teaching practice in basic education, such as a Base Nacional Comum Curricular, homologated at the end of 2017 replacing Parâmetros Curriculares nacionais and Orientações Curriculares para o Ensino Médio. After this stage, the intervention proposal was developed with the perspective of literary literacy and the methodological practice of the reading circle as a parameter, with a focus on the literature-cinema relationship so that it arouses in students the interest and pleasure in reading and sharing their experiences. impressions as they do when watching a movie. Among the methods of data collection, questionnaires and preparation of text / adaptation script were used based on authors such as Rildo Cosson and Syd Field. The theoretical contribution that supported the analyzes and the intervention proposal was based, mainly, in the studies of Graça Paulino, Rildo Cosson e Teresa Colomer in literary reading and literary literacy; in the field of receptionist theory contributions by Wolfgang Iser and Hans Robert Jauss; and in the area of audiovisual production, cinema and adaptation, and script writing, we have the studies of Robert Stam and Randal Johnson. After the analysis and intervention proposal, it was concluded that the methodology applied to the teaching of Literature in basic education has not been effective in stimulating the student to read. This research intends to contribute to reflections aiming at the analysis and methodological practices of literary reading, offering subsidies to professionals who want to develop these activities in the classroom, seeking to value Literature as an important factor of humanization, in addition to a source of aesthetic pleasure that can supplant school life and, in the act of reading, more present and constant in students’lives.